The Potency of Pesantren Economics: A Mapping Using R - Aisyah As-Salafiyah; Aam Slamet Rusydiana (The Economic Review of Pesantren, 2022)
The pesantren economy is currently one of the concerns of the Indonesian government, because pesantren are not only educational institutions but also have the potential to become business markets. Optimization of the role of Islamic boarding schools has been innovated in various programs, such as the Micro Waqf Bank proposed by the OJK or the Islamic Boarding School Holding launched by Bank Indonesia. The pesantren economy has also become one of the government's main instruments in developing the Islamic economy in Indonesia. This study tries to map the development of published research in the field of Islamic boarding school economics. The research was conducted using the R Biblioshiny application. The data analyzed was in the form of research publications related to the Islamic boarding school economy as many as 202 articles from 2011 to 2020. The results showed that the number of publications on the development of research results in the field of Islamic boarding schools economics had increased quite significantly, especially in the last 10 years and most of them were published in the Shirkah journal: Journal of Economics and Business and EDUKASI Journal of Religious and Religious Education Research. Other findings based on the results of text mining, the most researched issues related to the pesantren economy are related to the business fields carried out by pesantren, such as mini markets and trade, culinary, boarding schools/BMT, services, convection, agriculture, animal husbandry, fisheries, to the processing industry.